Systematic Literature Review : Pengaruh Bimbingan dan Konseling terhadap Perkembangan Sosial Emosional Peserta Didik - Arya Cakrabuwana; Cintia Vita Cahyani; Muhammad Nofan Zulfahmi (Jurnal Bintang Pendidikan Indonesia, 2025)
Guidance and counseling have a very important role in supporting students’ social emotional development, especially at the elementary school level. This service not only helps students understand themselves, but also develops social skills, increases self-confidence, and prepares them to face various challenges in educational and social environments. This research aims to analyze the impact of guidance and counseling on students’ social emotional development using the Systematic Literature Review (SLR) method. With a descriptive approach, this research examines various relevant and current literature to provide a deeper understanding of the effectiveness of guidance and counseling services in elementary schools. The research results show that the consistent application of guidance and counseling can improve students’ emotional, social and character capacities, which ultimately supports them to achieve optimal development. In addition, the presence of guidance and counseling teachers in elementary schools has proven to be very important to ensure that these services are implemented optimally, both in individual and group development. This research emphasizes the importance of collaboration between educators, counselors and policy makers in optimizing the implementation of guidance and counseling services as a strategy for building a generation that is independent, self-confident and has character.